Engineering the oleaginous yeast Yarrowia lipolytica for high-level resveratrol production - Sáez-Sáez, Javier; Wang, Guokun; Marella, Eko Roy; Sudarsan, Suresh; Cernuda Pastor, Marc; Borodina, Irina (Metabolic engineering, 2020)
Resveratrol is a plant secondary metabolite with multiple health-beneficial properties. Microbial production of resveratrol in model microorganisms requires extensive engineering to reach commercially viable levels. Here, we explored the potential of the non-conventional yeast Yarrowia lipolytica to produce resveratrol and several other shikimate pathway-derived metabolites (p-coumaric acid, cis,cis-muconic acid, and salicylic acid). The Y. lipolytica strain expressing a heterologous pathway produced 52.1 ± 1.2 mg/L resveratrol in a small-scale cultivation. The titer increased to 409.0 ± 1.2 mg/L when the strain was further engineered with feedback-insensitive alleles of the key genes in the shikimate pathway and with five additional copies of the heterologous biosynthetic genes. In controlled fed-batch bioreactor, the strain produced 12.4 ± 0.3 g/L resveratrol, the highest reported titer to date for de novo resveratrol production, with a yield on glucose of 54.4 ± 1.6 mg/g and a productivity of 0.14 ± 0.01 g/L/h. The study showed that Y. lipolytica is an attractive host organism for the production of resveratrol and possibly other shikimate-pathway derived metabolites. •Oleaginous yeast Y. lipolytica was engineered for production of aromatic compounds.•High resveratrol production required increased activities of Aro4p and Aro7p.•Multiple integration of resveratrol biosynthetic genes improved production.•Fed-batch fermentation enabled de novo production of 12.4 g/L resveratrol.